Chlorinated paraffins in nut-nougat and chocolate spreads from the German market. (March 2023) - Sprengel, Jannik; Rixen, Stefanie; Tietz, Thomas; Zellmer, Sebastian; Schumacher, David M.; Lüth, Anja; Kappenstein, Oliver; Vetter, Walter
Abstract: Chlorinated paraffins (CPs) are amongst the most discussed polyhalogenated pollutants in recent years. Their ubiquitous occurrence in the environment and especially foodstuff has given rise to concerns about CP uptake levels. Especially animal products and oils, i.e. foodstuff with high fat contents showed comparably high CP contaminations. In this study, nut-nougat and chocolate spread samples (n = 30) from the German market were analyzed on the occurrence of short-chain CPs (SCCPs) and medium-chain CPs (MCCPs) via gas chromatography coupled with electron capture negative ion mass spectrometry (GC/ECNI-MS). Fifteen (= 50%) of the samples contained CPs, with MCCPs being much higher abundant (17–270 ng/g fresh weight (fw)) in most samples than SCCPs (7.5–50 ng/g fw). No statistical correlation could be established between SCCP or MCCP occurrence on one hand and manufacturer or ingredients, such as palm oil on the other hand. A preliminary risk assessment of the detected levels gave margins of exposure (MOE) to CPs from consumption of chocolate and nut-nougat spreads ranging from approx. 16, 000 to 48, 000. Since health concerns are expected at an MOE of <1, 000, this indicated no risk from CP intake for the consumer by consumption of these products, based on current knowledge. Highlights: CPs were analyzed in 30 nut-nougat and chocolate spreads from the German market. Short-chain CPs (SCCPs) and medium-chain CPs (MCCPs) were separately quantified. Fifteen samples (50%) contained CPs between 7.5 and 270 ng/g fat. MCCPs were higher abundant than SCCPs in most samples. A preliminary risk assessment indicated no risk from CP intake for consumers.